Pengaruh Promsi dan Kualitas Produk Terhadap Keputusan Pembelian pada pelanggan PT. Biosafe Medan - Irene Nur Geofansa; Hery Syahrial; Isnaniah Isnaniah (Economics, Business and Management Science Journal, 2023)
The study purposes to identify : 1) the effect of promotion has a positive and significant influence towards the customer’s Buying Decision at PT. Biosafe Medan. 2) the effect of product quality has a positive and significant influence towards the customer’s Buying Decision at PT. Biosafe Medan. 3) the effect of both promotion and product quality has a simultaneous influence towards the customer’s Buying Ddecision at PT. Biosafe Medan. An associative study was conducted using population size as much as 26,275 employees. A total 100 respondents of PT. Biosafe Medan were chosen as the sampel by using random samplig method.  The  study  utilized the multiple linier regression  analysis as the data analysing technique. The dta of this study were gathered through interview and distributing questionnaire.  The  study  result  obtained  that  promotion  has  a  positif  and  significant influence towards the customer’s buying decision, where positive showed from the value 0,516 dan significant 0,000 0,05. Product quality has a positif dan significan influence towerds the customer’s buying decision, where positive showed prome the value 0,392 and significant 0,000 0,05. Both promotion and product quality has a positive and significant influence toweds the customer’s buying decision, where positif showed frome the value 2,711 and significant 0,000 0,05.